Experience of Radical Radiotherapy for Patients with Stages I-III Squamous Cell Carcinoma of the Glottic Larynx (Faridpur Medical College Journal, 2016)
This study was carried out from May 2012 to April 2013, on short term effects of Radical Radiotherapy for patients with Stages I-III squamous cell carcinoma of the glottic larynx at National Institute of Cancer Research and hospital, Mohakhali, Dhaka. A total of 50 biopsy proved squamous cell carcinoma of the glottis larynx were treated with radical Radiotherapy, total dose of which was 66Gy in 33 fractions over 7 weeks, conventionally fractionated with 200 cGy per fraction, one fraction per day and 5 fractions per week, using the machine 6 MV LINAC. The main outcome variables of the study were toxicities and clinical outcome of the patients. The peak age incidence was found in the age group of 51-60 years (56%). Among 50 patients, there were 82% males and 18% females and male to female ratio was 4.6:1. There were 86% found smokers and rests of the 14% patients were non smoker. Treatment related haematological and non-haematological acute and delayed toxicities were studied. Mucosities 28% (grade-II), skin reaction 78% (grade-II), anaemia 52% (grade-II), dysphagia 70% were the most common acute toxicities where as xerostomia 16% was the delayed side effect. With this treatment protocol, 86% patients responded completely.Faridpur Med. Coll. J. Jul 2015;10(2): 63-67